2006
DOI: 10.1007/s11262-005-5850-3
|View full text |Cite
|
Sign up to set email alerts
|

European and American Subgroup C Isolates of Avian Metapneumovirus belong to Different Genetic Lineages

Abstract: The gene encoding the attachment glycoprotein (G) was sequenced in three French isolates of-subgroup C avian metapneumovirus (APV-C) from ducks. With 1771 nt, this gene proved as long as recently published for North-American APV-C isolates from turkeys. The nt sequences of the duck viruses shared 99% identity but proved only 75-83% identical with their North-American counterparts, viruses of both origins encoding 585 amino acid (aa)-long G proteins. Alignments revealed more homogeneity within the European and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
55
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 19 publications
5
55
0
2
Order By: Relevance
“…Although aMPV subtype C recently emerged in commercial turkey farms, a survey conducted between 2000 and 2002 demonstrated that aMPV subtype C also infects wild birds (e.g., American coots, American crows, Canada geese, cattle egrets, and pigeons) in Georgia, South Carolina, Arkansas, and Ohio (53). Further, the appearance of aMPV subtype C outside the United States (in 1999 in France [51] and in 2005 in South Korea [30]) in different avian species suggests that this recently emerged subgroup of aMPV is geographically distributed across a wide range of avian hosts. Reports of aMPV during the seasonal outbreaks on several commercial turkey farms in and around Minnesota (22, 45,46), together with the recent findings of aMPV subtype C in wild avian species (53) and its wide geographic distribution (30, 51), suggest that this subtype could be a potential threat to poultry industries around the world.…”
mentioning
confidence: 99%
“…Although aMPV subtype C recently emerged in commercial turkey farms, a survey conducted between 2000 and 2002 demonstrated that aMPV subtype C also infects wild birds (e.g., American coots, American crows, Canada geese, cattle egrets, and pigeons) in Georgia, South Carolina, Arkansas, and Ohio (53). Further, the appearance of aMPV subtype C outside the United States (in 1999 in France [51] and in 2005 in South Korea [30]) in different avian species suggests that this recently emerged subgroup of aMPV is geographically distributed across a wide range of avian hosts. Reports of aMPV during the seasonal outbreaks on several commercial turkey farms in and around Minnesota (22, 45,46), together with the recent findings of aMPV subtype C in wild avian species (53) and its wide geographic distribution (30, 51), suggest that this subtype could be a potential threat to poultry industries around the world.…”
mentioning
confidence: 99%
“…after infection with four different aMPV/A isolates in two weeks old chicks (data not shown). Although another comparative study in turkeys did not indicate differences between aMPV/A and aMPV/B concerning respiratory signs (Van de Zande et al 1999), similar observations of differences in virulence between these subtypes were found in ducklings, turkeys, and broilers (Toquin et al 2006, Aung et al 2008. Thus, our data indicates differences in replication ability and virulence of type A and B aMPV in chicks.…”
Section: Discussionmentioning
confidence: 83%
“…aMPV subtypes A and B (aMPV/A and aMPV/B) are more widespread in the world, whereas subtype C is found in the United States and in domestic duck breeders in France (Toquin et al 2006) and subtype D was once reported in France (Cook et al 2000. In Brazil, where a high density of poultry farms exists, studies on chicken and turkey ϐlocks demonstrated a high prevalence of aMPV/A and aMPV/B infection , D' Arce et al 2005, with a higher number of aMPV/B circulating in the last years (Chacón et al 2011, Villarreal et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Based on antigenicity and genetic diversity, four subtypes of aMPV, designated A, B, C, and D, have been characterized (1,2,4). Subtypes A, B, and D are found mainly in Europe and Asia (5)(6)(7)(8). In the United States, aMPV was first identified in 1996, in a commercial turkey flock with respiratory diseases in Colorado (9).…”
mentioning
confidence: 99%
“…In the United States, aMPV was first identified in 1996, in a commercial turkey flock with respiratory diseases in Colorado (9). The virus was classified as subtype C due to its low sequence identity to subtype A and B viruses (6,9). Subsequently, it emerged in turkey flocks in Minnesota and became a major problem in the turkey industry in the United States (10,11).…”
mentioning
confidence: 99%